A look into education: Faith and Joy, the best possible education for the ones who are in the worst conditions. (Journal of Parents and Teachers, 2012)
An investment in quality is implicit in popular education. Further from the Access, popular sectors have the right to get a good education. It is no true that a bad education is better than no education. The best possible education for the ones who are in the worst conditions is better and necessary.
Keywords: opinion; Faith and Joy; Latinamerica; quality education.